Determination and evaluation of the thermophysical properties of an alkali carbonate eutectic molten salt. (20th May 2016) - An, Xuehui; Cheng, Jinhui; Zhang, Peng; Tang, Zhongfeng; Wang, Jianqiang
Abstract : The thermal physical properties of Li2 CO3 –Na2 CO3 –K2 CO3 eutectic molten salt were comprehensively investigated. It was found that the liquid salt can remain stable up to 658 °C (the onset temperature of decomposition) by thermal analysis, and so the investigations on its thermal physical parameters were undertaken from room temperature to 658 °C. The density was determined using a self-developed device, with an uncertainty of ±0.00712 g cm −3 . A cooling curve was obtained from the instrument, giving the liquidus temperature. For the first time, we report the obtainment of the thermal diffusivity using a laser flash method based on a special crucible design and establishment of a specific sample preparation method. Furthermore, the specific heat capacity was also obtained by use of DSC, and combined with thermal diffusivity and density, was used to calculate the thermal conductivity. We additionally built a rotating viscometer with high precision in order to determine the molten salt viscosity. All of these parameters play an important part in the energy storage and transfer calculation and safety evaluation for a system.